Narratives of the Unspoken in Contemporary Irish Fiction Silences that Speak - Caneda-Cabrera, M. Teresa; Carregal-Romero, José (New Directions in Irish and Irish American Literature, 2023)
XIX, 246 p. 2 illus., 1 illus. in color.